加工中心圆盘式刀库转动定位机构的设计计算 - 曹秋霞; 陈新亚 (Jixie chuandong)
The design and calculation method on rotating and locating mechanism of MCV2520 miniature vertical machining center’s circular tool magazine are introduced. The groove wheel’s working principle, calculation of structural parameter, and calculation and choose of tool magazine rotating motor are clarified.